Women rights in the Sudanese legislation - Fadel, Ibrahim Babaker Abdullah; Temsaah, Mohammed Hassan Jammaa; Abdullah, Abdul-Qadeem AbdulRahman (Arab Journal for Sciences and Research Publishing, 2017)
This study attempts to examine women rights in the Sudanese legislation and to show the attention that is being given to this issue. Descriptive analytical, deductive and inductive methods have been used to explore the legal texts as well as analyzing and interpreting them. The study showed that the Sudanese legislation covered most of the women rights, bearing in mind their particularity and role in society. The research has come up with some recommendations, of which it is important to reinforce women rights in a way that it ensures the protection of their rights, developing necessary measures to implement the legislative texts that respect women rights in practice, the pursuit of gender equality that does not conflict the essence of Islamic Sharia and women particularity.